Is rentier capitalism that bad? Rent, efficiency and inequality dynamics - MABROUK, Mohamed ben Ridha (Turkish Economic Review, 2018)
Abstract. The current economic context shows a tendency to inequality and rather weak growth. Rent-seeking behavior is often blamed for that. The purpose of this paper is to analyze the consequences, on the accumulation trajectory, of the existence of a rent levied by the rich on the poor. The model is inspired by the articles Stiglitz (1969), Schilcht (1975) and Bourguignon (1981). In particular, convex saving is used. We seek to see to what extent the introduction of a rent may call into question the Pareto-superiority of inequality proved by Bourguignon (1981) or alter the risk of decline highlighted in Mabrouk (2016). Within the limits of the assumptions of the model and of the numerical simulations carried out, we arrive at interesting and rather unexpected observations. Namely, a moderate rent levied by the rich on the poor may not only allow a Pareto-improvement of the economy and prevent the risk of decline, but also, it may unlock the economy from under-accumulation trap even if initial capital endowment is insufficient. The disadvantages of such a rent for the poor are felt only if the economy approaches or exceeds the golden rule where the net marginal productivity of capital is zero. Keywords. Inequality dynamics, Neoclassical growth, Rent, Efficiency. JEL. D99, E13, E21, E22, O41.